Research progress on RNA−binding proteins in breast cancer - Chen, Ying; Qin, Hai; Zheng, Lufeng (Frontiers in Oncology, 2022)
Breast cancer is the most common malignancy in women and has a high incidence rate and mortality. Abnormal regulation of gene expression plays an important role in breast cancer occurrence and development. RNA-binding proteins (RBPs) are one kind of the key regulators for gene expression. By interacting with RNA, RBPs are widely involved in RNA cutting, transport, editing, intracellular localization, and translation regulation. RBPs are important during breast cancer occurrence and progression by engaging in many aspects, like proliferation, migration, invasion, and stemness. Therefore, comprehensively understanding the role of RBPs in breast cancer progression can facilitate early diagnosis, timely treatment, and long-term survival and quality of life of breast cancer patients.